The complete mitochondrial genome of the blue skate Dipturus batis - Delaval, Aurelien Nicolas; Schwanck, Tanja; Kopp, Martina Elisabeth Luise; Hoarau, Galice Guillaume; Jones, Catherine S; Noble, Leslie Robert (Mitochondrial DNA Part B, 2020)
publishedVersion Paid Open Access